Modeling the effect of guanidinium in hybrid halide perovskites - Dahlgren Blumenau, Rickard (My University, 2025)
advancing solar cell technologies. However, they face many issues especially related to stability, since in general they easily degrade into photo-inactive phases due to environmental factors like temperature, humidity and light. It is thus of interest to understand the phase behaviors of these systems to be able to engineer stable perovskite solar cells with favorable optoelectronic properties. Two of the most promising organic halide perovskites for solar cells are MAPbI3 (MAPI) and FAPbI3 (FAPI). By mixing these it is possible to tune the optoelectronic properties and phase behavior. In recent studies it has been shown that incorporating GUAPbI3 (GUAPI) could further improve the optoelectronic properties by for instance increasing the charge carrier lifetime. However, the exact phase behaviors of these systems have not been investigated extensively. Thus, in this thesis the temperature dependence of the phase behaviors of mixed (MA,FA,GUA)PbI3 as well as each pure systems were investigated by training a neuro evolution potential (NEP) model on structural properties calculated through density functional theory (DFT). The model predicted the previously known phase behaviors of FAPI and MAPI. Additionally, the morphotropic phase boundary (MPB) between MAPI and FAPI was found around 21% of FAPI, which is in agreement with previous studies. GUAPI was found to adopt the a−a−a− phase at temperatures below 280K. Furthermore, it was found that adding GUAPI to (MA,FA)PbI3 the MPB shifted towards higher FAPI concentrations.
Keywords: neuro evolution potential, density functional theory, molecular dynamics, perovskites, guanidinium